The influence of stromal cells and tumor-microenvironment-derived cytokines and chemokines on CD3+CD8+ tumor infiltrating lymphocyte subpopulations. (3rd June 2017) - Koeck, Stefan; Kern, Johan; Zwierzina, Marit; Gamerith, Gabriele; Lorenz, Edith; Sopper, Sieghart; Zwierzina, Heinz; Amann, Arno
ABSTRACT: The tumor microenvironment has been identified as a major mediator of immunological processes in solid tumors. In particular, tumor-associated fibroblasts are known to interact with tumor infiltrating immune cells. We describe the influence of fibroblasts and tumor-microenvironment-derived cytokines on the infiltration capacity of CD3 + CD8 + cytotoxic T lymphocyte subpopulations using a multicellular 3D co-culture system. 3D tumor microtissues were cultivated using a hanging drop system. Human A549 and Calu-6 cancer cell lines were incubated alone or together with the human fibroblast cell line SV80 for 10 d to form microtissues. On day 10, peripheral blood mononuclear cells (PBMC) were added with or without cytokine stimulation for 24 h. Infiltrating PBMC subpopulations were investigated by flow cytometry. Aggregation of the microtissues and the infiltration of the PBMCs were analyzed by immunohistochemistry, and endogenous cytokine and chemokine expression was analyzed with a multi-cytokine immunoassay. Secretion of chemokines is increased in microtissues consisting of cancer cells and fibroblasts. PBMC infiltrate the whole spheroid in cancer cell monocultures, whereas in co-cultures of cancer cells and fibroblasts, PBMCs are rather localized at the margin. Activated CD69 + and CD49d + T lymphocytes show an increased microtissue infiltration in the presence of fibroblasts. We demonstrate that the stromal component of cancer microtissues significantly influences immune cell infiltration. The presence of fibroblasts in cancer microtissues induces a shift of T lymphocyte infiltration toward activated T lymphocytes.